The two-echelon inventory-routing problem with fleet management - Schenekemberg, Cleder M.; Scarpin, Cassius T.; Pécora, José E.; Guimarães, Thiago A.; Coelho, Leandro C. (Computers & operations research, 2020)
•We introduce fleet management in the context of inventory-routing.•We study different combinations of inventory policies and fleet management costs.•We design a matheuristic and a hybrid parallel exact algorithm based on branch-and-cut.•We validate our algorithms on a special case of our problem from the literature, obtaining all BKSs.•We show that a more complex logistics system leads to greater efficiency in logistics operations. This paper introduces the Two-Echelon Inventory-Routing Problem with Fleet Management. This problem arises under a two-echelon vendor-managed inventory system when a company must make vehicle routing and inventory management decisions, while renting a fleet subject to short- and mid-term agreements. Different chemical products are transported contaminating the vehicles that may require cleaning activities. Pickups of input take place in the first echelon, and the final product deliveries are performed in the second echelon. Based on a real-life case in the petrochemical industry, we introduce a formulation that takes into account vehicle rentals, cleanings, transportation, inventory management, and vehicle returns decisions. We design a branch-and-cut algorithm to solve it and also propose a matheuristic, in which vehicle routes are handled by an adaptive large neighborhood mechanism, while input pickups, product deliveries, and fleet planning are performed by solving several subproblems to optimality. Moreover, we introduce a hybrid parallel framework, combining our matheuristic and the branch-and-cut algorithm in order to solve very large instances exactly. We validate our methods by solving a set of instances of the two-echelon multi-depot inventory-routing problem from the literature, obtaining new best solutions for all instances. We have introduced a set of instances for this rich and new problem, and performed an extensive assessment of our methods. The results provide interesting data about the supply chain structure.